Longitudinal Correlates of Maternal Involvement and Spanking in Spanish-speaking Latinas Who Have Experienced Intimate Partner Violence - Stein, Sara F. (Journal of interpersonal violence, 2022)
Mothers experiencing intimate partner violence (IPV) have been found to have negative long-term parenting outcomes, such as reduced maternal involvement and greater use of physical punishment, which represent potential pathways by which IPV negatively affects children. Factors influencing these parenting practices have not been examined in IPV-exposed Latinas. The aim of this study is to understand the factors that affect maternal involvement and spanking by Latinas to contribute to culturally-informed intervention development and refinement. A total of 93 Spanish-speaking Latinas who had experienced IPV completed standardized measures of maternal involvement, spanking, IPV, depression, and posttraumatic stress (PTS) and provided demographic information. Slightly over half of the women participated in an intervention program. Longitudinal multilevel modeling (MLM) demonstrated that higher levels of maternal depression predicted lower levels of involvement over time. PTS reexperiencing symptoms were positively related to involvement, such that mothers with higher levels of reexperiencing reported higher levels of involvement. An independent longitudinal MLM revealed that higher amounts of IPV exposure and higher levels of PTS arousal symptoms were associated with higher levels of spanking, while maternal employment was associated with lower levels of this same parenting behavior. Maternal involvement increased over time, where there was no significant change in spanking over time, and no effect of the intervention program on either parenting practice. Results suggest clinical interventions should target reductions in depression and specific PTS symptom subdomains as pathways to improving parenting in IPV-exposed Latinas. Continued study is needed to understand the relationship between reexperiencing and maternal involvement.